Student union election survey 1969 - Petersson, Olof (University of Gothenburg, 1996)
In connection with the election to the student union in April 1969, students at Göteborg University were asked a number of questions concerning their university studies, the UKAS-reform, student union politics and politics in general. Questions about the respondent´s university studies included major financing of studies, other minor sources of income, work besides studies during semester, opinion on economic situation, housing and opinion on housing, number of semesters at the university, subject(s) studied present semester, subjects with marks, university degree intended, opinion on one´s own study results, future occupation and opportunity to get a job after finished education. A new university reform, UKAS, were introduced in the fall of 1969. The respondents were asked about their knowledge of the UKAS-reform, how they were informed about the reform, things considered good and bad respectively in the UKAS-reform, and personal attitude towards the reform. Other questions dealt with the respondent´s interest and involvement in student politics, opinion on how student issues are treated and how they could be dealt with in a better way. Questions were asked about participation in the student union election, student party voted for, things considered positive and negative with party voted for, party considered as second best, worst and second worst. The respondents also had to state if they voted in the last general election, party voted for, present party preference, interest in politics, self-placement on a left-right scale, self-rated change of political opinion, dailies read regularly, attitude on Vietnam, attitude on the ASEA involvement in the Cabora Bassa project in Mocambique, and participation in demonstrations.

In connection with the election to the student union in April 1969, students at Göteborg University were asked a number of questions concerning their university studies, the UKAS-reform, student union politics and politics in general. Questions about the respondent´s university studies included major financing of studies, other minor sources of income, work besides studies during semester, opinion on economic situation, housing and opinion on housing, number of semesters at the university, subject(s) studied present semester, subjects with marks, university degree intended, opinion on one´s own study results, future occupation and opportunity to get a job after finished education. A new university reform, UKAS, were introduced in the fall of 1969. The respondents were asked about their knowledge of the UKAS-reform, how they were informed about the reform, things considered good and bad respectively in the UKAS-reform, and personal attitude towards the reform. Other questions dealt with the respondent´s interest and involvement in student politics, opinion on how student issues are treated and how they could be dealt with in a better way. Questions were asked about participation in the student union election, student party voted for, things considered positive and negative with party voted for, party considered as second best, worst and second worst. The respondents also had to state if they voted in the last general election, party voted for, present party preference, interest in politics, self-placement on a left-right scale, self-rated change of political opinion, dailies read regularly, attitude on Vietnam, attitude on the ASEA involvement in the Cabora Bassa project in Mocambique, and participation in demonstrations.
Kårvalsundersökningen 1969
Keywords: Higher and further education; Gymnasial och högre utbildning; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap